SISTEM PAKAR DIAGNOSIS KERUSAKAN PADA TELEVISI (TV) TABUNG MENGGUNAKAN METODE FORWARD CHAINING - Maisyaroh Maisyaroh; Ridwan Septianto (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2016)
Television (TV) as one of the electronic devices that have long working hours not be surprised if found damage mild to severe in the use of television, users who do not really understand the damage TV will usually immediately call a repair service or bring it to a repair shop TV. We recommend that we should be able to know what damage occurred on TV that we had. In order not to repeat the same mistakes, which makes the TV was broken, as well as in terms of cost, if we can examine and analyze the damage to the TV itself, we do not need to bring it to a TV repair shop. This expert system application using the way of thinking an expert in making a diagnosis of damage. This application helps seek damages conclusion of the categories of damage suffered. This application is created using forward chaining method, which is a process of inference that starting the search from the fact that there is to get a final conclusion. Making this expert system application using Microsoft Visual Basic 6.0 and to its database using Microsoft Access 2010.